Pave way for Semantic Digital Libraries - Tajer, Pegah; Nikseresht, Alireza (Qualitative and Quantitative Methods in Libraries, 2019)
Semantics and accessibility are naturally part of HTML by design. Therefore, there is a must to significantly leverage the standard markup language and write the cleanest code possible. The purpose of this work is performing HTML validity check in terms of compliance with W3C standards for home pages of Iranian digital and electronic libraries in order to pave way for applying semantic technologies in Iranian Library websites. This is a comparative survey. 82 library software-based digital libraries and 68 electronic libraries were identified via Google search in the domains of .ir, .ac.ir, .org and .com. Data collected via an automatic tool developed by authors in which W3C Markup Validation Service is used for validation tests. Besides, total tags of URLs are counted through it to be able to normalize HTML error frequencies for each home page. Data were analyzed using nonparametric tests via IBM SPSS Statistics 20. Validation test results in about 50 percent failure rate. 38 out of 70 valid libraries are digital libraries and 32 are electronic ones. Mean of HTML error has dramatically decreased in 2017 in comparison with 2015; however Standard Deviation has increased sharply. Moreover, the distribution of HTML error scores is similar across digital and electronic libraries. Regarding conformance to HTML standards, it seems essential to revise the web design of Iranian digital and electronic libraries to fulfill semantic web potentialities.